Modernization of Islamic Education in Bibliometric Review - Asari, Hasan; Ritonga, Maisaroh; Nursalimah, Nursalimah; Megawati, Betti; Ruwaidah, Ruwaidah (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
In recent years, calls for the modernization of Islamic education have expanded their focus beyond the levels of basic and secondary education to include Islamic university institutions. Studies on Islamic education are particularly noteworthy when presented in the form of bibliometric analysis. The purpose of this study is to create a map of research trends in bibliometrics that pertain to the process of modernizing Islamic education. This research, which relies on data, examines the number of articles on modernizing Islamic education that have been published in various countries throughout the world. The Dimensions database was used in the study dataset, which was then analyzed using Bibliometrix utilizing R-Tool and displayed with Vosviewer. The findings of the bibliometric mapping of research on modernizing Islamic education using Biblioshiny and VOSviewer yielded 197 relevant articles in 160 journals between 1965 and 2022. Mukhibat, Hidayatulla Azra, and La Hadisi were the top three authors on this topic. The majority of research trends, as illustrated by the visualization of data from VOSviewer, are associated with Islamic Education. The phrases